2023
DOI: 10.1186/s12958-023-01063-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of granulocyte colony-stimulating factor for infertility undergoing IVF: a systematic review and meta-analysis

Abstract: Objective This study aimed to evaluate the effectiveness of granulocyte colony-stimulating factor (G-CSF) for infertility and recurrent spontaneous abortion. Methods Existing research was searched in PubMed, Embase and Cochrane Library till Dec 2021. Randomized control trials (RCTs) that compared G-CSF administration with the control group in infertility women undergoing IVF were included. The primary outcomes included clinical pregnancy rate; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…But Pourmoghadam, Z. et al also found that the miscarriage rate was significantly decreased in the PBMC-treated group than the non-treated group, which did not reach significance in our study [ 16 ]. A meta-analysis consisting of 20 RCTs found that G-CSF increased the biochemical pregnancy rate, embryo implantation rate, and clinical pregnancy rate [ 81 ]. Another meta-analysis found G-CSF administration may improve clinical pregnancy rate, but it concluded that they were uncertain whether the administration of G-CSF improves ongoing pregnancy or overall clinical pregnancy rates or reduces miscarriage rate compared to no treatment or placebo for the included studies had unclear allocation concealment or were at high risk of performance bias [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…But Pourmoghadam, Z. et al also found that the miscarriage rate was significantly decreased in the PBMC-treated group than the non-treated group, which did not reach significance in our study [ 16 ]. A meta-analysis consisting of 20 RCTs found that G-CSF increased the biochemical pregnancy rate, embryo implantation rate, and clinical pregnancy rate [ 81 ]. Another meta-analysis found G-CSF administration may improve clinical pregnancy rate, but it concluded that they were uncertain whether the administration of G-CSF improves ongoing pregnancy or overall clinical pregnancy rates or reduces miscarriage rate compared to no treatment or placebo for the included studies had unclear allocation concealment or were at high risk of performance bias [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential intervention is the use of granulocyte colony stimulating factor (GCSF), which has shown promise in improving endometrial thickness and pregnancy outcomes in cases of thin endometrium and recurrent implantation failure (RIF) but not in general population [24]. However, more research, including randomized controlled trials, is needed to establish its e cacy and determine the appropriate patient population for GCSF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF is a strong inhibitor of cytotoxic NK cell function [ 268 ], which is necessary for the uterine receptive milieu. The success of G-CSF in increasing pregnancy rate has been reviewed in detail (i.a., in [ 267 , 269 , 270 ]). Although not all studies found an improving effect of intrauterine perfusion of G-CSF [ 271 , 272 , 273 ].…”
Section: Clinical Significance In Reproductive Medicinementioning
confidence: 99%
“…Recurrent implantation failure Thin endometrial lining Scratching [171][172][173][174][175][176][177][178], PRP infusion [183][184][185][186][187][188], G-CSF [267,269,270] Wound-healing-like Decidualization, Regeneration…”
Section: Balanced Inflammatory Micromilieumentioning
confidence: 99%